The magnitude of and health system responses to the mental health treatment gap in adults in India and China. Issue 10063 (17th December 2016) - Patel, Vikram; Xiao, Shuiyuan; Chen, Hanhui; Hanna, Fahmy; Jotheeswaran, A T; Luo, Dan; Parikh, Rachana; Sharma, Eesha; Usmani, Shamaila; Yu, Yu; Druss, Benjamin G; Saxena, Shekhar
Summary: This Series paper describes the first systematic effort to review the unmet mental health needs of adults in China and India. The evidence shows that contact coverage for the most common mental and substance use disorders is very low. Effective coverage is even lower, even for severe disorders such as psychotic disorders and epilepsy. There are vast variations across the regions of both countries, with the highest treatment gaps in rural regions because of inequities in the distribution of mental health resources, and variable implementation of mental health policies across states and provinces. Human and financial resources for mental health are grossly inadequate with less than 1% of the national health-care budget allocated to mental health in either country. Although China and India have both shown renewed commitment through national programmes for community-oriented mental health care, progress in achieving coverage is far more substantial in China. Improvement of coverage will need to address both supply-side barriers and demand-side barriers related to stigma and varying explanatory models of mental disorders. Sharing tasks with community-based workers in a collaborative stepped-care framework is an approach that is ripe to be scaled up, in particular through integration within national priority health programmes. India and China need to invest in increasing demand for services through active engagement with the community, to strengthen service user leadership and ensure that the content and delivery of mental health programmes are culturally and contextually appropriate.